Multidimensional assessment of older adults in situations of vulnerability in the context of Primary Health Care (Research, Society and Development, 2025)
Population aging in Brazil intensifies the demand for strategies within Primary Health Care (PHC) to identify vulnerability and preserve functional capacity in older adults. Objective: To assess the functional capacity of older adults in situations of vulnerability followed by a Primary Health Unit in Juiz de Fora, Minas Gerais, and to describe associations with frailty, depressive symptoms, and fall risk. Methods: This was a cross-sectional observational study including individuals aged 60 years residing in the catchment area of a Primary Health Unit. Sociodemographic and clinical characterization of participants was conducted using the Elderly Health Handbook, which enabled the collection of personal data, assessment of functional capacity, and identification of health vulnerability through the Vulnerable Elderly Identification Protocol. In addition, the 20-item Clinical-Functional Vulnerability Index (IVCF-20), the Timed Up and Go (TUG) test, and the Geriatric Depression Scale were applied. Results: Vulnerable older adults had a higher mean age compared with non-vulnerable individuals, as well as higher proportions of functional decline, frailty, depressive symptoms, and increased fall risk. Discussion: Findings suggest an overlap among vulnerability, frailty, impaired mobility, and mental health burden, underscoring the need for systematic screening and multiprofessional interventions in PHC. Conclusion: Multidimensional assessment is a key strategy for identifying and delivering longitudinal care for vulnerable older adults, supporting the planning of actions to preserve autonomy and quality of life.